Domestic Violence against Women - Saili, Jamayah; Mahfoz,, Napsiah; Labong, Elicabet Pasan; Putit, Zabidah (2014)
Domestic violence is a global issue that cuts across cultures and boundaries. Domestic violence needs to be addressed seriously irrespective of the cultural norms of a society that prevents us to recognize the prevalence and widespread existance of this problem. This paper will discuss on domestic violence against women in eastern society. Discussion on the nature of domestic violence is followed by a case study that highlights the pain and anguish suffered by the victims in Malaysia. Focus of analysis in the case study will be on the types of violence against women and coping strategies adopted by the abused in the ‘culture of silence’ as according to Hofstede (1984), traditional Asian values of privacy, honor, self-restraint, harmony, and order. Finally, this paper highlights the importance of empowering women through education and training.